2010
DOI: 10.3171/2009.6.jns09483
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular coil occlusion of 152 middle cerebral artery aneurysms: initial and midterm angiographic and clinical results

Abstract: S urgical clipping of MCA aneurysms is usually preferred to EVT. This preference is largely the result of a relatively easy surgical access and unfavorable endovascular approach due to the complex branching pattern of the MCA. As of this writing, no direct comparison between results of endovascular and surgical treatment of MCA aneurysms has been published in the literature, leaving the optimal treatment strategy unclear and choices depending mainly on the practice at the different centers. We therefore consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 17 publications
1
59
2
5
Order By: Relevance
“…6 However, most of these series were highly focused on selected patients. [7][8][9][10] To date, with the advent of new endovascular tools such as balloons and stents designed specifically for the intracranial circulation, MCA aneurysms can be managed by means of the endovascular approach. However, the safety and efficacy of EVT for all patients are not well known yet.…”
mentioning
confidence: 99%
“…6 However, most of these series were highly focused on selected patients. [7][8][9][10] To date, with the advent of new endovascular tools such as balloons and stents designed specifically for the intracranial circulation, MCA aneurysms can be managed by means of the endovascular approach. However, the safety and efficacy of EVT for all patients are not well known yet.…”
mentioning
confidence: 99%
“…Favorable clinical outcomes (mRS, 0 -2 and GOS, 5) in other large series of ruptured MCA aneurysms comprising at least 50 patients treated with EVC, are within the 67%-85% range. [10][11][12][13][14] In the present study, the largest published single-center experience to date, patients with consecutive ruptured MCA aneurysms achieved good outcome (GOS, 5) in 70.3% and favorable outcome (GOS, 4 and 5) in nearly 80%, with the proportion of favorable presenting clinical grade patients (WFNS, 1-2) being 72%. We were able to directly compare the results of our present study to a large audit of ruptured aneurysms at all locations treated through EVC at our institution with similar distribution of clinical grade.…”
Section: Clinical Outcome In Patients With Ruptured Aneurysmsmentioning
confidence: 88%
“…The perforation rate lies within the range of previously published studies that have demonstrated procedural perforation complicating 1%-8.5% of MCA aneurysm treatments. [10][11][12][13][14]32 In 2 large prospective series of unruptured aneurysms (ATENA) 45 and ruptured aneurysms (CLARITY) treated by endovascular means, the perforation rate for MCA aneurysms was 4.1% and 8.5%, respectively. We have previously suggested that the rate of aneurysmal perforation may be higher at the MCA location 15 ; we demonstrated that MCA aneurysms accounted for 13% of cases but 24% of all intraprocedural ruptures.…”
Section: Morbidity and Mortality Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The current literature focusing on angiographic recanalization after coil embolization includes numerous and different strategies for image interpretation, including those done at the treating facility as well as those in a core laboratory. In addition, some reported studies rely on single observers, [9][10][11] whereas others report multiple-reader outcomes. [12][13][14] However, the impact of setting (site readings vs core facility interpretation) as well as singlereader vs multiple-reader studies remains poorly studied.…”
mentioning
confidence: 99%